A Review: The Development of Metamaterial Absorber - Ali, Siti Adlina MD; Abu, Maisarah; Zabri, Siti Normi (International Journal of Integrated Engineering, 2020)
Metamaterials is an artificial resonant structure that is designed to obtain specific characteristics which are not naturally occurring in nature. One such applications is metamaterials absorber, which offers benefits over conventional absorbers. Metamaterials absorber is the structure that attenuates the energy in electromagnetic waves. The structure will soak up the incident energy, convert into heat and reduce the energy reflected back to the source. Various designs on metamaterials absorber have been investigated exhibiting different characteristics; single-band, dual-band, as well as broadband. Starting from rigid substrates, followed by a thin, an ultra-thin and also flexible substrate materials are being considered. Perfect absorbency achieved as the surface impedance of the structure equal to free space impedance. Different methods on determined the loss in absorber; lumped resistor, resistive patterns and lossy dielectric. These unique characteristics of metamaterials absorber enabling its wide applications in various technologies